2016
DOI: 10.1038/srep35786
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized magnetic nanowires for chemical and magneto-mechanical induction of cancer cell death

Abstract: Exploiting and combining different properties of nanomaterials is considered a potential route for next generation cancer therapies. Magnetic nanowires (NWs) have shown good biocompatibility and a high level of cellular internalization. We induced cancer cell death by combining the chemotherapeutic effect of doxorubicin (DOX)-functionalized iron NWs with the mechanical disturbance under a low frequency alternating magnetic field. (3-aminopropyl)triethoxysilane (APTES) and bovine serum albumin (BSA) were separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
94
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 49 publications
9
94
0
Order By: Relevance
“…This coating step, can chemically stabilize magnetic particles against degradation as a function of time. In addition, coating can be used for 1 3 the functionalization of the nanoparticles surface, where different substances and ligands can be added to enhance the colloidal stability and targeting specificity [11].…”
Section: Introductionmentioning
confidence: 99%
“…This coating step, can chemically stabilize magnetic particles against degradation as a function of time. In addition, coating can be used for 1 3 the functionalization of the nanoparticles surface, where different substances and ligands can be added to enhance the colloidal stability and targeting specificity [11].…”
Section: Introductionmentioning
confidence: 99%
“…High‐aspect‐ratio magnetic NW arrays are normally produced by template‐assisted deposition . When dissolving the template to work directly with the NWs, the whole structure collapses into a bunch of individual NWs without support, which makes it possible to be studied or used individually but makes their handling and integration into devices quite complex. Therefore, a further step in the research of magnetic NWs is to produce structures of interconnected wires at the nanoscale, as proposed, for example, in the first patent of the race‐track memory by IBM but never fabricated.…”
mentioning
confidence: 99%
“…It demonstrated that neither the static magnetic field nor the rotating one results in any cell damage, as quantified by measuring the cells' metabolic activity (relative to untreated control cells) the day after the magnetic stimulations. The nanorods/cell membrane interactions thus do not induce any significant alteration of cells viability and proliferation capacity, even in the rotating setting, contrary to some other studies reporting membrane physical rupture triggered by rotating magnetic nanoparticles, generally targeted to a specific receptor . Here, it shows that cells can also adapt to a rotating stress and avoid massive harm.…”
mentioning
confidence: 48%
“…In magnetic manipulation of cell membranes, an external rotating magnetic field is used to act at a distance, with precisely controlled intensity, direction, and localization of the applied magnetic torque. Magnetically driven rotating or oscillating magnetic nanoparticles could thus be used to probe cells' mechanical properties, to deliver drugs, or to kill cells by physical membrane rupture . In this last application, anisotropic nanoparticles in disk‐ or rod‐like shapes, stimulated with low‐frequency magnetic fields, could compromise the cell membrane and thereby trigger apoptotic or necrotic programed cell death.…”
mentioning
confidence: 99%